Contribution of Hepatitis B Virus Infection to the Aggressiveness of Primary Liver Cancer: A Clinical Epidemiological Study in Eastern China - Yang, Fan; Ma, Longteng; Yang, Yuan; Liu, Wenbin; Zhao, Jun; Chen, Xi; Wang, Mengchao; Zhang, Hongwei; Cheng, Shuqun; Shen, Feng; Wang, Hongyang; Zhou, Weiping; et al. (Frontiers in Oncology, 2019)
Background & Aims: Contribution of hepatitis B virus (HBV) infection to the aggressiveness of primary liver cancer (PLC) remains controversial. We aimed to characterize this in Eastern China. Methods: We enrolled 8515 PLC patients whose specimens were reserved at the BioBank of the hepatobiliary hospital (Shanghai, China) during 2007-2016. Of those, 3124 who received primary radical resection were involved in survival analysis. A nomogram was constructed to predict the survivals using preoperative parameters. Results: Hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC), and combined hepatocellular cholangiocarcinoma (CHC) accounted for 94.6%, 3.7%, and 1.7%, respectively. The rates of HBV infection were 87.5%, 49.2%, and 80.6%, respectively. HBV infection was significantly associated with 10 years earlier onset, more cirrhosis, higher α-fetoprotein, higher carbohydrate antigen 19-9 (CA19-9), more microvascular invasion (MVI), lower neutrophil-to-lymphocyte ratio (NLR), and lower platelet-to-lymphocyte ratio (PLR) in HCC. HBV infection was also associated with 7 years earlier onset, more cirrhosis, higher α-fetoprotein, more MVI, and lower PLR in ICC. In the multivariate Cox analysis, high circulating HBV DNA, α-fetoprotein, CA19-9, NLR, tumor size, number, encapsulation, BCLC stage, and MVI predicted an unfavorable prognosis in HCC; only CA19-9 and BCLC stage, rather than HBV-related parameters, had prognostic values in ICC. A nomogram constructed with preoperative HBV-related parameters including HBV load, ultrasonic cirrhosis, and α-fetoprotein perform better than the current staging systems in predicting postoperative survival in HCC. Conclusion: HBV promotes the aggressiveness of HCC in Chinese. Contributions of HBV to ICC and other etiological factors to HCC might be indirect via arousing non-resolving inflammation.